2013
DOI: 10.1037/a0031595
|View full text |Cite
|
Sign up to set email alerts
|

Children's use of moral behavior in selective trust: Discrimination versus learning.

Abstract: Does valence play a role in children’s sensitivity to and use of moral information in the service of selective learning? In the present experiment, we explored this question by presenting three- to five-year-old children with informants who behaved in ways consistent or inconsistent with socio-moral norms, such as helping a peer retrieve a toy, or deliberately tearing a peer’s artwork. ‘Good’ versus ‘bad’ informants were contrasted with putatively neutral-behaving informants. In an effort to specify the role t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 43 publications
3
35
1
1
Order By: Relevance
“…When provided with evidence of speaker morality in the absence of other relevant speaker characteristics, findings suggest that, by 4 years of age, children generally prefer to learn from an individual judged to be nicer (Doebel & Koenig, 2013;Mascaro & Sperber, 2009). Yet, when children receive additional information about speakers, evidence of their good intentions and moral warmth enters into a wider network of considerations.…”
Section: Negativity Biasmentioning
confidence: 92%
See 1 more Smart Citation
“…When provided with evidence of speaker morality in the absence of other relevant speaker characteristics, findings suggest that, by 4 years of age, children generally prefer to learn from an individual judged to be nicer (Doebel & Koenig, 2013;Mascaro & Sperber, 2009). Yet, when children receive additional information about speakers, evidence of their good intentions and moral warmth enters into a wider network of considerations.…”
Section: Negativity Biasmentioning
confidence: 92%
“…However, it is unclear whether young children's selective trust in a moral speaker is attributable to a specific preference for a moral speaker or vigilance against an immoral speaker. Doebel and Koenig (2013) investigated this issue by familiarizing preschoolers to either a moral speaker or an immoral speaker, each of whom was paired with a neutral speaker. Children exhibited a clear negativity bias when asked to discriminate the nicer of the two speakers: they showed enhanced performance when discriminating between immoral and neutral behavior relative to when discriminating between moral and neutral behavior.…”
Section: Negativity Biasmentioning
confidence: 99%
“…One of the prerequisites of learning from testimony is that we must trust what others tell us, but such trust need not be blind. There are many strategies one could use for discriminating trustworthy informants from untrustworthy ones, and children seem to adopt these strategies prior to formal schooling, preferring informants who are knowledgeable (Birch, Vauthier, & Bloom, 2008), familiar (Corriveau & Harris, 2009), consistent (Pasquini, Corriveau, Koenig, & Harris, 2007), and moral (Doebel & Koenig, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the finding regarding speaker certainty was expected, the finding for speaker benevolence was somewhat surprising. After all, Doebel and Koenig (2013) had demonstrated that a speaker who displayed well-intentioned, helpful behaviour towards a peer was considered to be reliable in his object labelling. Moreover, Landrum et al (2013) showed that benevolence was even a more important factor than expertise.…”
Section: Resultsmentioning
confidence: 99%
“…Benevolent speakers thus seem to be trusted more by children than malevolent speakers in a general sense, but there is also evidence to suggest that speaker morality may guide children's novel word learning. Doebel and Koenig (2013) found that children were more inclined to acquire novel labels from well-intentioned speakers (who had previously been seen to engage in prosocial behaviour towards peers) over those of a neutral speaker, and the labels of a neutral speaker over those of an ill-intentioned speaker (who had previously displayed antisocial behaviour towards peers). Similarly, Landrum, Mills, and Johnston (2013) showed that the labels of informants who were described as being prosocial ("This person is very nice.…”
Section: Speaker Competence and Benevolence Cues In Word Learningmentioning
confidence: 98%